Assessment of coral reef health and resilience in Saobi and Sapapan Islands, Kangean Archipelago, Indonesia - AHMAD HANDOKO; ZAINUL HIDAYAH; DIAN SAPTARINI; DWI BUDI WIYANTO; JIHANNUMA ADIBIAH NURDINI; DEDI SETIAWAN; LUCAS DE OLIVEIRA VIEIRA (Society for Indonesian Biodiversity, 2025)
Abstract. Handoko A, Hidayah Z, Saptarini D, Wiyanto DB, Nurdini JA, Setiawan D, Vieira LDO. 2025. Assessment of coral reef health and resilience in Saobi and Sapapan Islands, Kangean Archipelago, Indonesia. Biodiversitas 26: 3545-3559. Coral reef ecosystems in East Java are inadequately documented due to the lack of long-term monitoring and conservation programs, such as COREMAP, in comparison to the eastern region of Indonesia. This study aimed to assess the condition, conservation status, and resilience capacity of coral reef ecosystems on small islands. The research was conducted in the remote areas of Saobi and Sapapan Islands, situated to the east of mainland Madura Island, East Java, Indonesia. The percentage of benthic cover was measured in three stations on Sapapan Island and four stations on Saobi Island using the Underwater Photo Transect (UPT) method. The resilience of the coral reef ecosystem was evaluated by calculating the percentages of fleshy seaweed cover, rubble, and live coral cover. Also, the Conservation Class (CC) was determined by looking at the types of coral, which are categorized as Ruderals (r), Competitors (K), and Stress-tolerators (S) using the rKS ternary diagram. The results showed that based on the percentage of live coral cover, the benthic ecosystems of Saobi and Sapapan Islands are in moderate to excellent condition, with average live coral covers of 58.01±10.15 and 70.02±14.40, respectively. Coral lifeforms with a fairly high percentage and dominating the benthic habitat on both islands include Coral Branching (CB), Coral Massive (CM) and Coral Foliose (CF). Coral reef ecosystems in both islands showed a strong ability to recover, as shown by a high percentage of live coral cover and very little fleshy seaweed cover (3%) and coral rubble (60% or less). The rKS diagram showed that the coral reef ecosystems on Sapapan and Saobi Islands are classified as CC2 for conservation, meaning they have more than 60% Competitor-type coral (K) and over 50% live coral cover. These results suggest that the environmental conditions in the study area continue to support the coral reef growth.